Ação coletiva passiva : possibilidade de aplicação para tutela dos direitos metaindividuais - Cruz, Carlos Wagner Araújo Nery da (2015)
This paper has as fundamental objective to show the feasibility of Defendant Class Action for the protection of meta individual rights, even though the Institute is still not specifically provided in the collective process of micro in Brazil. Passing through the origin of collective actions, supported in actiones popularis of Roman law, the defendant class action provided for in the Federal Rules of Civil Procedure served as initial paradigm for the Institute's analysis, whereas the action shall apply in the common law system, especially in the United States of America. The current legal scenario and the complexity of social conflicts demonstrate the need to broaden the knowledge about ways to protect rights under the cloak of trans-individuality, despite the non-existence of a national Code of Collective Procedures. Accordingly, it is suggested to overcome the instrumentalist stage of the process towards instrumentalism constitutional form as a way of approximation of procedural law, in particular of collective procedural law, the constitutional text and, consequently, the effective application of the hermeneutic gap for collective action. In the study, the labour process served as a paradigm of reception of collective actions, even if they occur with groups in the passive pole or legitimized in active pole, showing up as a starting point for understanding the legitimacy of groups, categories or classes, also for other branches of law. Finally, it is suggested that, through various examples, it is already possible to use passive collective action in Brazil, even with the absence of specific rules about this issue, the principle of collective due process of law and effectiveness of collective judicial protection.